UPAYA PENINGKATAN HASIL BELAJAR DENGAN MENGGUNAKAN MEDIA PETA DAN GAMBAR PADA MATA PELAJARAN IPS DIKELAS V SD NEGERI 02 MUARA PANAS KECAMATAN BUKIT SUNDI KABUPATEN SOLOK - Fidrawati Fidrawati (Pedagogi: Jurnal Ilmu Pendidikan, 2015)
Eeffort improve result learn student by using map media and Picture at subject of IPS in SDN 02 Muara panas of the fifth class, bukit sundi subdistrics in solok regency. Media very needed study to especially study of IPS do not monotone and drag on. Picture and map represent one of the media study of which can used to water down student comprehend Lesson of IPS. Pleasant study will generate separate fascination to student so that/ to be study take place better and can reach the target of which is expected. problems which is raised in this research is do usage of map media and picture can improve result learn student at subject of IPS in struggle items all area figure fight against colonization of Dutch and Japan at student class V SDN 02 Muara panas of the fifth class, bukit sundi subdistrics in solok regency. research which is writer use is method research of class action that is a study done/conducted by research which also as class teacher to improve; repair performance in order to improving result learn which with quality, this research procedure is done/conducted in two cycle, every cycle divided to become four activity type that is planning phase, execution, and observation of reflex. in activity of research of writer cooperate with collage as observer.